2013
DOI: 10.1039/c2cc38254g
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic cell-mediated three-dimensional assembly of halloysite nanotubes

Abstract: Biomimetic architectural assembly of clay nanotube shells on yeast cells was demonstrated producing viable artificial hybrid inorganic-cellular structures (armoured cells). These modified cells were preserved for one generation resulting in the intact second generation of cells with delayed germination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 25 publications
(12 reference statements)
2
91
0
2
Order By: Relevance
“…4 Similarly, HNTs exhibit no toxicity towards Escherichia coli bacteria 32 and yeast cells. 33 Fahkrullin et al 7 reported the first example of the evaluation of halloysite toxicity in vivo on free living nematodes (worms) Caenorhabditis elegance. The authors demonstrated that HNTs were found exclusively in the intestines of the worms and no nanotubes were detected outside the intestines of the nematodes (Fig.…”
Section: Halloysite Biocompatibilitymentioning
confidence: 99%
“…4 Similarly, HNTs exhibit no toxicity towards Escherichia coli bacteria 32 and yeast cells. 33 Fahkrullin et al 7 reported the first example of the evaluation of halloysite toxicity in vivo on free living nematodes (worms) Caenorhabditis elegance. The authors demonstrated that HNTs were found exclusively in the intestines of the worms and no nanotubes were detected outside the intestines of the nematodes (Fig.…”
Section: Halloysite Biocompatibilitymentioning
confidence: 99%
“…7(e) and 7(i)), suggesting that internalization may also contribute to the distribution of MNPs between proliferating cells. Growing and dividing cells are expected to gradually shed external surface coatings, as known from microbial cells [33]. Apart from highly visible aggregated MNPs localized on perinuclear areas, we expected to detect isolated nanoparticles on distal areas of cells.…”
Section: Proliferation Of Pah-mnps-coated Cellsmentioning
confidence: 99%
“…3,4 In this context, being biocompatible nanomaterials, 5,6 HNTs are mainly employed for the encapsulation of biologically active molecules, [7][8][9] biomedical implants 10,11 and controlled drug delivery. 12 Furthermore, thanks to their structural features, HNTs are suitable for a potential application as support for catalytic composites.…”
mentioning
confidence: 99%